Immuno‐Spin Trapping Method for the Analysis of S‐Nitrosylated Proteins. Issue 9 (27th September 2021) - Sircar, Esha; Stoyanovsky, Detcho A.; Billiar, Timothy R.; Sengupta, Rajib
Abstract: The dynamic and unstable nature of protein nitrosothiols (PSNOs) derived from complex biological matrices (like cell lysates) make them unsuitable for proteomic/biochemical analysis in vitro . In an attempt to increase the stability of cell‐derived PSNOs, scientists have devised methods to derivatize thiols undergoing nitrosylation, with a suitable molecule, to yield a stable adduct that could easily be detected using appropriate antibodies. The Biotin Switch Assay (BTSA) is currently the most widely used method for tagging PSNOs; however, the error‐prone and cumbersome nature of the BTSA protocol prompted the development of alternative mechanisms of tagging cell‐derived PSNOs. One such method is the immuno‐spin trapping method using 5, 5‐dimethyl‐1‐pyrroline N‐oxide (DMPO), which effectively overcomes the shortcomings of the BTSA and proves to be a promising alternative. Here we describe the protocol for DMPO‐based PSNO labeling and subsequent proteomic analysis by western blotting with an anti‐DMPO antibody. © 2021 Wiley Periodicals LLC. Basic Protocol : Labeling of cell‐derived PSNOs by DMPO‐based immuno‐spin trapping and their subsequent analysis by immunostaining